Infantile hepatic hemangioma complicated consumptive hypothyroidism - Qianlong Liu; Xinkui Guo; Xin He; Na Liu; Jing Shi; Yan Geng; Ping Cao (Elsevier, 2021)
Infantile hepatic hemangioma (IHH) is the most common benign liver tumor in infancy, some life-threatening complications like abdominal compartment syndrome, consumptive hypothyroidism and cardiac failure may occur in these patients. Hypothyroidism should be focused on and managed earlier to prevent intellectual and growth retardation. We described a 4 months old infant complaint of progressive abdominal distention, who was diagnosed with diffuse hepatic hemangiomas by ultrasonography and MRI, treated successfully with propranolol and levothyroxine for consumptive hypothyroidism. At 8 months old levothyroxine was stopped, she grew up with a normal growth trajectory and neurodevelopment at her last follow-up at the age of 13 months. Our study suggests that thyroid function should be evaluated even though negative neonatal screen and propranolol should be first-line agent for diffuse IHH. It is instrumental that simultaneous anti-tumor and thyroid replacement make diffuse IHH patients with consumptive hypothyroidism recovery better.